Profile of competencies and employability from the perspective of the graduate in tourism - Carbajulca-Milla, Milady (2023)
The globalized environment, increasingly demanding, with dizzying changes, a constant advance in technology and a highly competitive labor market, forces us today to a permanent development and adaptation of competencies to the needs and changes of the environment. The development of competencies is linked to the level of employability of people in the labor market, since a better trained person with adequate competencies can have a better performance in his or her job. This article is based on research aimed at determining how the competency profile is related to the employability of the tourism graduate of the University National Santiago Antúnez de Mayolo (UNASAM), with the purpose of making known the competencies to improve the level of employability, and to promote the development and revaluation of the professional in this sector. The findings of the research show that the profile of competencies is poorly suited to the needs of the tourism labor market and that graduates have difficulties in their employability due to the general training they receive, lacking adequate specialization, little practical experience due to the lack of workshops implemented that would allow an approach to the tools, techniques and methodologies of the areas of tourism, poor management of information technologies applied to tourism and lack of knowledge of the requirements of employers to support training needs and promote labor market insertion and professional competitiveness.